Metformin Inhibits HaCaT Cell Proliferation Under Hyperlipidemia Through Reducing Reactive Oxygen Species via FOXO3 Activation - Zhang L; Liu X; Huang M; Wang R; Zhu W; Li Y; Shen L; Li C (Dove Medical Press, 2022)
Li Zhang,1 Xiaoling Liu,1 Min Huang,1 Rui Wang,1 Wenwei Zhu,1 Yu Li,2 Lin Shen,1 Chengxin Li1 1Department of Dermatology, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People's Republic of China; 2Department of Dermatology, The Fifth Medical Center of Chinese PLA General Hospital, Beijing, 100853, People's Republic of ChinaCorrespondence: Chengxin Li, Department of Dermatology, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People's Republic of China, Tel +86 15210866656, Email chengxinderm@163.comPurpose: Metformin (MET) has been proved to be effective for the treatment of psoriasis. The mechanisms of its action under the hyperlipidemia have yet to be fully elucidated. Here, we investigated the effect of metformin on the cell proliferation induced by hyperlipidemia and the underlying mechanism in immortalized human keratinocyte cell line (HaCat).Methods: Wild-type or FOXO3 knockdown HaCat cells were treated with free fatty acids (FFA) for 10 days and then co-treated with metformin for another 4 days. Triglyceride (TG) level, cell viability, proliferation, apoptosis, antioxidant enzymes, reactive oxygen species (ROS) levels, as well as the transcription activity of FOXO3 were analyzed.Results: Metformin decreased HaCaT cell proliferation and induced cell apoptosis after FFA treatment. Metformin was found to significantly increase the expressions and the activities of superoxide dismutase (SOD) as well as catalase (CAT), and reduced the reactive oxygen species (ROS) level. Metformin significantly promoted the autophagy and increase FOXO3 protein level in the nucleus under hyperlipidemia. However, all of the effects from metformin were partially blocked by FOXO3 knockdown.Conclusion: This study demonstrated that under the hyperlipidemia, metformin has significant antiproliferation and proapoptosis effects by reducing ROS level as well as increasing autophagy. All of these effects from metformin were through FOXO3-dependent pathway.Keywords: reactive oxygen species, ROS, apoptosis, autophagy, forkhead box O3, FOXO3